2007
DOI: 10.1086/518653
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Decoupling of Globular Clusters with the Extended Horizontal Branch

Abstract: About 25% of the Milky Way globular clusters (GCs) exhibit unusually extended color distribution of stars in the core helium-burning horizontal-branch (HB) phase. This phenomenon is now best understood as due to the presence of helium enhanced second generation subpopulations, which has raised a possibility that these peculiar GCs might have a unique origin. Here we show that these GCs with extended HB are clearly distinct from other normal GCs in kinematics and mass. The GCs with extended HB are more massive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
144
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(161 citation statements)
references
References 32 publications
(45 reference statements)
14
144
1
2
Order By: Relevance
“…These artificially younger ages may also result from the presence of multiple stellar populations, since Balmer lines are mostly sensitive to the main-sequence turn-off temperature (Worthey 1994). In our Galaxy, the most massive GCs also show indications of unusually hot, extended HBs, multiple stellar populations, and are kinematically distinct from other Galactic GCs (Recio-Blanco et al 2006;Lee et al 2007). Spectroscopic studies have shown that three types of GC populations exist in M 31: old objects with a wide range of metallicities, intermediate age and metallicity GCs, and young GCs with slightly higher metallicity (Perrett et al 2002;Beasley et al 2004Beasley et al , 2005Fusi Pecci et al 2005;Puzia et al 2005a).…”
Section: Agesmentioning
confidence: 65%
“…These artificially younger ages may also result from the presence of multiple stellar populations, since Balmer lines are mostly sensitive to the main-sequence turn-off temperature (Worthey 1994). In our Galaxy, the most massive GCs also show indications of unusually hot, extended HBs, multiple stellar populations, and are kinematically distinct from other Galactic GCs (Recio-Blanco et al 2006;Lee et al 2007). Spectroscopic studies have shown that three types of GC populations exist in M 31: old objects with a wide range of metallicities, intermediate age and metallicity GCs, and young GCs with slightly higher metallicity (Perrett et al 2002;Beasley et al 2004Beasley et al , 2005Fusi Pecci et al 2005;Puzia et al 2005a).…”
Section: Agesmentioning
confidence: 65%
“…About a quarter of all globular clusters exhibit an unusually extended horizontal branch (Lee et al 2007). This "blue hook" morphology probably indicates that such clusters had an unusual evolutionary history.…”
Section: Flattening and Horizontal Branch Morphologymentioning
confidence: 99%
“…Currently available observational data on the phasespace structure of the Galactic stars show signatures of such accretion events of dSphs, as evidenced by the spatial distribution and stellar populations of halo globular clusters (Searle & Zinn 1978;Mackey & Gilmore 2004;Lee et al 2007), streams/overdensities in the spatial distribution of stars (Ibata et al 1994;Newberg et al 2002;Majewski et al 2003;Jurić et al 2008), kinematic substructures (Helmi et al 1999 …”
Section: Introductionmentioning
confidence: 99%